Políticas de descentralização da educação no Brasil e em Portugal: avanços e recuos da desconcentração de poderes - Donaldo Bello de Souza; Dora Fonseca Castro; Luís Rothes (Universidade do Minho, 2013)
This paper discusses, from a comparative perspective, the decentralization of education in Brazil and Portugal since the 1990s. Supported on relevant literature and on its legal framework, the researchers seek to investigate the interinstitutional and sociopolitical relations that mediate this process, in Brazil, under the collaboration regime and, in Portugal, among the relations between central and local power. The general conclusion notes that, although both central governments have generalized the decentralization discourse for some time now, it seems that the level of rhetoric has failed to be effectively overcome, due to a number of advances and setbacks. Attempts have constituted some devolution of power, still marked by the same centralizing logic, outcome of both countries historical and social heritage (their previous dictatorial regime), and currently under the modulation of neoliberal economic policies.